Impact of Communicative Culture in Teaching Spanish - Galeeva, Alsu Ilgizarovna; Gataullina, Veronika Lubimovna (Journal of History Culture and Art Research, 2019)
So far, in science, the process of learning foreign languages and the process of development for individuals’ communicative culture has been considered separately. In this study, the possibility of communicative culture development in teaching Spanish was defined. In the national tradition the methods of teaching Spanish are not represented as widely as, for example, the methods of teaching English, German, and French. There is a need for research on this topic. In this paper the process of learning was studied, not only from the point of view of linguistics properly but also from the point of view of the development of culture, in particular the communicative culture of students. The aim of this research was to study the theoretical literature on the stated topic, to conduct an ascertaining experiment using a questionnaire among students studying Spanish as a specialty, on the topic “Student’s communicative culture”. According to the results of the experiment we succeeded: - to establish the content of the concept of communicative culture in the understanding of students; - find out which of its components have greatest importance from their point of view; - to determine the students’ opinion on the existence of a connection between learning Spanish as a specialty and the development of a communicative culture, and also to establish how this relationship is expressed; - check whether students are aware of the methodology by which they are taught Spanish, and whether they know that this technique is a communicative technique.